Serological evidence of clade Ib Mpox transmission by sex workers and within household in South Kivu, DRC - Leandre Murhula Masirika; Luca M. Zaeck; Pacifique Ndishimye; Jean Claude Udahemuka; Saria Otani; Frank M. Aarestrup; Leonard Schuele; Babs E. Verstrepen; Scott Jones; Ashley Otter; Corine H. GeurtsvanKessel; Jean Pierre Musabyimana; et al. (Nature Communications)
Abstract Understanding secondary attack rates is a key knowledge gap in the ongoing clade Ib mpox virus (MPXV) outbreak in the Democratic Republic of the Congo. Here, we report the first cross-sectional serological study to investigate local MPXV clade Ib transmission in South Kivu, DRC. Seropositivity was defined as a detectable titer in a cell lysate-based screening ELISA and confirmation by virus neutralization test. Sera were collected in November and December 2023 (n = 120), and in May 2024 (n = 48) from professional sex workers (PSW) and visitors of 25 bars with reports of mpox cases. We detected serological evidence for MPXV infection in 18% and 17% of these sera, respectively, indicating that PSW played an important role in MPXV clade Ib transmission in this region. Additionally, sera from 108 direct contacts of mpox cases from 34 households were collected between September 2023 and May 2024. Serological evidence for MPXV infection was found in at least one serum sample in 50% of households, including in nine households with seropositive minors, providing evidence for close-contact household transmission. Serological studies are needed to comprehend the extent and severity of the ongoing MPXV outbreak, and may be used to guide targeted vaccination strategies, particularly for high-risk groups.